Type 5 diabetes: fifth pillar or fifth column - Sanjay Kalra; Sambit Das; Saptarshi Bhattacharya (Journal of the Pakistan Medical Association, 2025)
This opinion piece reviews the history of malnutritionrelated, or malnutrition modulated diabetes mellitus(MMDM). It reviews various terms used to describe thiscondition, and analyzes current efforts at renaming it astype 5 diabetes. It provides a simple, yet effectivediagnostic checklist, based upon Ahuja’s diagnosticcriteria, for MMDM. While research is certainly required todefine and describe this entity, renaming it will createconfusion and chaos, rather than comprehension orclarity. Keywords: Diabetes, malnutrition, MMDM, MRDM,pancreatic diabetes, PDDM, PDPM, tropical diabetes